Systemic Reformulation of Labour Arrangements Between Demand and Pressure Concerning Income towards Welfare in Indonesia - Sulaiman, Abdullah (Jurnal Cita Hukum, 2020)
AbstractsThe abstract of this article authors several points, among others: Firstly, Purpose of Article; to analyze labor regulation concerning income provision towards welfare for employers in Indonesia. Secondly, Scope of Work; that the legal implementation focuses on Indonesian labor law arrangements, and then concerning pressures relevant to income as an international standard for laborers, and demand for wage acceptance as a facility for labor welfare, and also labor law dispute settlement in the Indonesian welfare system. Thirdly, Legal Methodology; refers to qualitative research with secondary materials from normative and empirical sources, also by conducting legal comparison from other countries outside of Indonesia. Fourthly, Result in Summary; on the systemic implementation of Indonesian labor regulation as stipulated in a written constitution, that ”Each citizen shall reserve the rights for adequate employment and income based on sustainable standards (Article 27 paragraph (2), 1945 Indonesian Constitution). The income pressure for International labor standards via ILO has created a standard system to protect the rights of laborers binding themselves in an agreement, based on ILO Convention No.89 the Year 1949 which instigated the birth of Law Number 18 the Year 1956 concerning Ratification of ILO Convention No. 80 the Year 1957. Demands for income to be accepted as labor welfare has yet to reiterate the importance of wage component in applicable labor law (Law Number 13 the Year 2003 concerning Employment) since it allows Governor in each province to regulate the measurement of labor’s wage on annual basis. Similarly with labor trial pattern which only allows the Industrial Relations Court and not solely referring to labor arbitration institution as expected from ILO and WTO as international organizations. Fifthly, Conclusion; that systemic reformulation of labor regulation to achieve welfare in Indonesia still requires the participation or internal demand from laborers and pressure from international labor institutions.Keywords: Income Regulation, Indonesian Labour Welfare. Reformulasi Sistemik Pengaturan Ketenagakerjaan Antara Permintaan dan Tekanan Terkait Pendapatan untuk Kesejahteraan di IndonesiaAbstrakTujuan Penulisan artikel ini untuk menganalisis pengaturan perburuhan dalam pemberian penghasilan menuju kesejahteraan oleh pengusaha di Indonesia. Sedang ruang Lingkupnya bahwa pelaksanaan hukum pengaturan hukum perburuhan Indonesia, kemudian terhadap tekanan mengenai penghasilan dari standar buruh Internasional, dan tuntutan penerimaan penghasilan sebagai fasilitas kesejahteraan buruh, juga sistem penyelesaian hukum perburuhan dalam sistem kesejahteraan di Indonesia. Metode Penelitian digunakan adalah menggunakan cara penelitian kualitatif dengan bahan sekunder dari bahan hukum normatif dan empiris, juga melakukan perbandingan hukum dari luar Indonesia. Hasilnya bahwa terhadap penerapan sistemik pengaturan perburuhan Indonesia yang telah dijabarkan dalam konstitusi tertulis menekankan bahwa” tiap-tiap warga negara berhak atas pekerjaan dan penghidupan yang layak bagi kemanusiaan” (Pasal 27 ayat (2) UUD 1945). Tekanan penghasilan dari standar buruh Internasional melalui ILO telah menciptakan suatu sistem standar melindungi hak buruh mengikatkan diri di dalam perjanjian yang konvensi ILO No.89 Tahun 1949 mengenai lahir UU No.18 Tahun 1956 tentang Persetujuan Konvensi ILO No.80 Tahun 1957. Tuntutan penerimaan penghasilan sebagai kesejahteraan buruh belum memberikan penegasan komponen upah dalam perundang buruh berlaku (UU No.13 Tahun 2003 tentang Ketenagakerjaan) karena memberikan pada setiap pemerintahan Gubernur setiap provinsi untuk mengatur besar-kecil pengupahan buruh untuk setiap tahunnya.Kata Kunci: Pengaturan Penghasilan, Kesejahteraan Buruh Indonesia. Системное изменение условий труда между спросом и давлением в отношении доходов для обеспечения благосостояния в ИндонезииАннотацияЦель исследования: проанализировать трудовые условия при предоставлении дохода для обеспечения благосостояния предпринимателями в Индонезии. Предмет исследования: выполнение и условие трудового законодательства  Индонезии, затем давление на доход со стороны международных трудовых стандартов и требования о принятии дохода в качестве объекта социальной сферы для рабочих, и также системы урегулирования трудового законодательства в системе социального обеспечения в Индонезии. Используемые методы исследования: качественный метод исследования с использованием вторичных материалов из нормативных и эмпирических правовых материалов, а также в проведении юридических сравнений за пределами Индонезии. Результаты исследования: применение индонезийских трудовых норм, описанных в писаной конституции, подчеркивают, что « каждый гражданин имеет право на труд и достойную жизнь для человечества» (пункт (2) статьи 27 Конституции 1945 года). Давление на доходы со стороны международных трудовых стандартов через МОТ привело к созданию стандартной системы защиты прав трудящихся в соответствии с Конвенцией МОТ № 89 от 1949 года о принятии Закона № 18 от 1956 года об Утверждении Конвенции МОТ № 80 от 1957 года. Что касается благосостояния рабочих, он не подтвердил компонент заработной платы в применимом трудовом законодательстве (Закон № 13 от 2003 года о рабочей силе), поскольку он даёт правительству каждого губернатора каждой провинции право регулировать сумму заработной платы на каждый год. Точно так же модель трудового правосудия допускает только PPHI (Разрешение Производственных Споров), а не единственное учреждение арбитражного урегулирования трудовых конфликтов, как ожидается от мировых учреждений МОТ и ВТО.Ключевые слова: Управление доходами, Благосостояние индонезийских рабочих.